2023
DOI: 10.1097/pec.0000000000002911
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ear Nose Throat Consultations Requested From the Pediatric Emergency Service in a Tertiary Hospital

Abstract: ObjectiveThe aim of this study is to examine the reasons and the methods of approach to the patients for the ear nose and throat (ENT) consultations requested from the patients who applied to the pediatric emergency department.MethodsThe files of 351 patients who applied to the pediatric emergency outpatient clinic and were asked for consultation from the ENT clinic were reviewed retrospectively. Demographic data, complaints on admission, diagnostic examinations, diagnoses, treatment methods, and hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Bei der Behandlung von Kindern in Notfallsituationen nehmen Fremdkörper in Gehörgang, Nase, Hypopharynx, oberem Ösophagus und den unteren Atemwegen einen wichtigen Raum ein, in dem HNO-Ärzte oftmals wichtige Notfallkompetenzen nicht nur im stationären Sektor, sondern auch in der ambulanten Versorgung stellen [25,37,38]. Eine sichere Entfernung von Ohrfremdkörpern bei Kindern durch Nicht-HNO-Ärzte wird allein aus Irland beschrieben [39].…”
Section: Einführungunclassified
“…Bei der Behandlung von Kindern in Notfallsituationen nehmen Fremdkörper in Gehörgang, Nase, Hypopharynx, oberem Ösophagus und den unteren Atemwegen einen wichtigen Raum ein, in dem HNO-Ärzte oftmals wichtige Notfallkompetenzen nicht nur im stationären Sektor, sondern auch in der ambulanten Versorgung stellen [25,37,38]. Eine sichere Entfernung von Ohrfremdkörpern bei Kindern durch Nicht-HNO-Ärzte wird allein aus Irland beschrieben [39].…”
Section: Einführungunclassified
“…Additionally, it has been observed that vitamin D promotes the production of reactive oxygen species, known as oxidative burst, as well as antimicrobial peptides, including cathelicidin and lactoferrin. These components are crucial in effectively eliminating bacteria (Syed et al,2020;Auala et al,2022;Murdoch et al,2019). Interleukin-37 (IL-37) is a recently discovered cytokine that belongs to the interleukin-1 family.…”
Section: Introductionmentioning
confidence: 99%